Real world mathematics : the design of mathematics trails - Soh, Karen Jasmine. (2008)
This study investigated the role mathematics trails have in influencing students’ attitude toward mathematics and in enhancing their appreciation of mathematics. The sample for the study came from a class of 42 students in a Primary 6 EM1 stream. The development of the trail spanned a period of 6 months. The students were guided in the development of the trail where necessary. The final trail consisted of 10 stations that were located around the school.